Effect of endotracheal intubation versus laryngeal mask airway on patient’s quality of voice and swallowing - Sõber, Linda; Lepner, Urmas; Kirsimägi, Ülle; Kasenõmm, Priit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The aim of our study was to evaluate postoperative voice and swallowing disorders during the first postoperative week and to compare these findings between two anesthesia methods: endotracheal intubation tube (ETI) and laryngeal mask airway (LMA). Methods: We conducted a prospective cohort study of patients who underwent laparoscopic cholecystectomy with ETI (n=103) and patients who underwent open hernioplasty or lower extremity varicectomy with LMA (n=100). All subjects underwent preoperatively and during the first postoperative week laryngeal imaging by videolaryngostroboscopy (VLS), filled in subjective evaluations of voice and swallowing complaints. In addition, acoustic voice analysis (AVA), maximum phonation time (MPT) measurement and perceptual voice evaluation were conducted. Results: VLS showed visual changes in pharyngeal and laryngeal anatomy in 4 (4%) patients of the LMA group and 14 (13.6%) patients of the ETI group (p=0.02). No statistically significant postoperative subjective voice and swallowing changes were found in either group. In female patients AVA showed a statistically significant increase of the SPI value in the ETI group (p=0.037). In male patients we noted an increase in mean fundamental frequency (F0) and decrease in MPT with both ventilation methods. Conclusions: Both investigated ventilation methods can be regarded as practically equal. Although clinical signs showed more intense trauma in the ETI group, objective measurements and patient subjective evaluation of voice and swallowing function were similar in both groups.